About some approaches modeling of the vehicle on simulator - V. G. Mikhailov (Системный анализ и прикладная информатика)
The purpose of the given work is consideration and working off of approaches, techniques, schemes of realisation of modelling of the vehicle on simulators on the basis of a choice of more perfect models of movement, fluctuations, roadability of the vehicle in package Matlab/Simulink for reception and an estimation of parametres of the vehicle, it loading. Features of imitating modelling of the vehicle on a simulator, requirements to it, using methods of such modelling on the basis of computer models, hydropulsators and a moving platform with the monitors/projectors, simulating road conditions where reactions to it of the driver, movements essentially influencing modes and loading the vehicle with the further use of the received data at bench tests are considered are considered. Mathematical models of the tyre, movement, fluctuations, the roadabilities of the vehicle providing more correct modelling in real time are developed.New approaches and technique in realisation of imitating modelling of movement, roadability and loading the vehicle, based on combined use of the powerful computer and minicomputer Raspberry for reading of parametres of controls, steering of visualisation of road conditions, module S-Function Builder created ON on С/C++ both an incorporated file longinal profile and a microprofile of real road, the information interchange organisation through three general files on SD disk Raspberry with certain periodicity (5 Hz) are offered, the block diagramme in Matlab/Simulink and is developed software. By the spent modelling of the vehicle 6х6 with ma = 21200 kg it is established that it has fuel consumption of km of 63,56 l/100, average speed of 66,1 km/h and number of switchings of a check point 7 (at t> 10 c). And basically check point switching occurs on last 3 higher drives.